A NARRATIVE INQUIRY OF PRE-SERVICE ENGLISH TEACHERS’ EXPERIENCES IN TEACHING GRAMMAR DURING THE COVID-19 PANDEMIC - Nita Nur Aeny; Elih Sutisna Yanto; Yousef Bani Ahmad (Linguistik : Jurnal Bahasa dan Sastra, 2021)
This narrative study aimed to investigate pre-service English teachers experiences in teaching practicum that focused in teaching grammar during the COVID-19 pandemic. This study was conducted by using narrative inquiry as the research design. The participants of this study were two pre-service teachers of English Education Department of UNSIKA who experienced in teaching practicum in seventh semester especially in teaching grammar during the COVID-19 pandemic in Indonesia. The data related to this study collected using reflective journal, interview, and artifacts. The data that has been collected were analyzed using thematic analysis (Braun and Clarke, 2006). The findings show that (1) the pre-service English teachers tend to use deductive rather than inductive approach in teaching grammar in secondary school during the COVID-19 pandemic. (2) Teaching grammar is very beneficial for pre-service English teachers to enrich their knowledge and teaching skill related grammar. (3) Teaching grammar during the COVID-19 is challenging for pre-service English teachers since some of them are still not superb at grammar. In addition, technical problems such as unstable internet connection and audio issues is resulted grammar teaching ineffective. These findings have implications for pre-service English teachers and students in grammar teaching context.